HUBUNGAN STRES KERJA DENGAN KESEJAHTERAAN PSIKOLOGIS GURU - Flaviani Nathania Leonardi; Niken Widi Astuti (Fakultas Psikologi Universitas Tarumanagara, 2023)
The background of this research is to see that teaching is a profession with a high level of stress. When a teacher has a high level of stress, this will affect the individual teacher's well-being. This study aims to see whether there is a relationship between work stress and the psychological teacher's well-being. This research is a quantitative study using a purposive sampling technique, with a survey method using a questionnaire and g-form. The questionnaires used were the Job Stress Scale by Parker & Decotiis (1983) and Ryff's Psychological Well Being Scale by Ryff (1995). This study involved 385 teacher participants aged 21 to 60 years. This research was conducted for approximately 4 months starting from September 2022 to December 2022. The results of the correlation test using the Pearson Correlation Test, show that there is a negative relationship between work stress and psychological well-being. Negative work relationship means, the higher the teacher stress, the lower the teacher's psychological well-being.